Evaluating the Effectiveness of the KP4 Model for School Governance Quality Improvement: The Role of School Management and Community Participation in 3T Regions - Aslam; Nurafni; Syahrial Syah; Fitri Alyani; Hella Jusra; Evy Segarawati Ampry; Diki Rukmana (Universitas Sulawesi Barat, 2026)
This study examines the effectiveness of the KP4 model comprising participative leadership, collaborative planning, inclusive organization, and community based monitoring and evaluation in improving school governance in a 3T (underdeveloped, frontier, and outermost) context. Employing a mixed methods approach Quantitative data were analyzed using descriptive statistics, followed by qualitative analysis to explain the statistical trends. Integration was conducted through connecting and merging procedures, where interview findings were used to interpret and validate quantitative results, the study integrates quantitative data from 30 respondents with qualitative insights from in depth interviews involving eight key informants, including school leaders, teachers, administrative staff, and community representatives. Quantitative findings reveal an overall mean score of 3.957, indicating that the implementation of the KP4 model is effective and approaches a “very good” level. The strongest dimensions are collaborative planning and participative leadership, which significantly enhance stakeholder engagement and organizational coherence. Qualitative findings further confirm that the model fosters shared responsibility, strengthens school–community collaboration, and promotes a transparent and inclusive organizational culture. However, the monitoring and evaluation dimension remains relatively underdeveloped, particularly in terms of data-driven and technology-supported practices. The study contributes to the literature by proposing an integrative governance model that aligns leadership, organizational processes, and community participation, particularly in resource constrained educational settings. The findings suggest that the KP4 model can serve as a scalable framework for improving school quality, although further development of digital based evaluation systems is necessary to ensure sustainability.